Laser intrastromal keratomileusis for high myopia and myopic astigmatism. Issue 3 (1st March 1997) - Condon, P I; Mulhern, M; Fulcher, T; Foley-Nolan, A; O'Keefe, M
Abstract : BACKGROUND: Laser intrastromal keratomileusis (LASIK) is an evolving technique which enables high degrees of myopia (>8.0 dioptres) and myopic astigmatism to be corrected. This paper describes initial experience with this procedure. It also details the methodology, the results, the problems encountered, and discusses retreatment procedures. METHODS: 51 eyes (48 primary cases and three retreatments) underwent LASIK for simple myopia or compound myopic astigmatism. After the keratotomy was fashioned with a Chiron corneal shaper, the ablation was performed with either a Summit or Meditec excimer laser. The actual preoperative astigmatism ranged from −0.5 D to −6.0 D (in the astigmatic myopic LASIK (AML) series), while the range of preoperative myopia in the combined myopic LASIK (ML) and AML series was −8.0 D to −37.0 D. Of the ML cases, group 1 (−8.0 to −15.0 D (dioptres)), group 2 (> −15.0 to −20.0 D), and group 3 (> −20.0 D) had mean preoperative myopia values (spherical equivalent) of −11.26 D, −16.84 D and −27.78 D. The same groupings (1, 2, and 3) for the AML cases had respective values of −9.702, −17.4, and −23.08. In the AML series the mean preoperative astigmatism was −2.109 D. Follow up ranged from 8 to 27 months (mean 15.8 months). Six of the cases required retreatment. RESULTS: There was a reduction in best corrected visual acuity (BCVA) (of 1 Snellen line) in seven of the primary cases (14.5 %) (three in the ML group and four in the AML group), and in one of the retreatment cases. The BCVA improved in 28 cases (58%) in the primary treatment group. The mean correction attempted (spherical equivalent) for the ML groups 1, 2, and 3 was 10.51 D, −14.5 D, and −27.78 D, versus a mean correction achieved of −9.445 D, −15.625 D, and −21.571 D. Similarly, for the AML groups, attempted correction values were −9.702 D, −17.4 D, and −23.08 D, while the values achieved were −6.95 D, −51.425 D, and −15.708 D. Regression was minimal and stabilisation of the refractive result was achieved in all groups, except group 3 of the ML series, by the 3 month examination period. The mean postoperative astigmatism in the AML series was −0.531 D. Vector analysis of the AML series showed that the mean surgically induced astigmatism was +0.93 D. The most common complication encountered was undercorrection, which occurred in 35 cases—23 cases in the ML group and 12 cases in the AML series. Twenty eight per cent of the ML cases, and 25% of the AML cases were within plus or minus 1.5 D of the attempted refraction. CONCLUSION: For the correction of high myopia and myopic astigmatism, LASIK results in less postoperative pain and relatively little subepithelial haze compared with high myopic photorefractive keratectomy. Furthermore, a stable refraction and reasonably predictable outcome occurs much earlier. High myopia up to −37.0 D can be corrected, albeit with some limitations at the extremes of myopia—in terms of the amount of myopia correctable; this represents a limitation of the technique. Retreatment is a technically straightforward and effective way to treat undercorrection. Undercorrection, the main complication seen in our series, should become less common when the ablation algorithms are further refined.